Torfowiska i zasoby wodne złóż torfowych w województwie lubuskim = Peatlands and water resources of peat deposit in the lubuskie voivodship - Lipka, Krzysztof; Bargiel, Tomasz; Boroń, Krzysztof; Klatka, Sławomir (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Based on improved inventory materials the total water resources in peat deposits in the Lubuskie province were determined. The aim of the work was the enrichment of quality and quantity characteristics of natural environment in the Western Poland.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)